A Study to Assess the Stress and Anger Management by Deep Breathing Exercise and Meditation Among Adolescent Nursing Students at a Selected Nursing School in Delhi - Sarita Upadhyaya (International Journal of Evidence Based Nursing And Practices, 2024)
Introduction: Stress is a response that can lead to physical, emotional, or psychological strain. It is a frequent occurrence in daily life. Stress acts as the body's natural mechanism for defense against potential threats and dangers. It initiates a release of hormones that ready the body's functions to either confront danger head-on or retreat, commonly known as the fight-or-flight reaction. Anger can be caused by both external and internal events such as stress, family issues, abuse, poor social, financial situations, overwhelming of time and energy, non-appreciation of effort and opinion, injustice, loss of energy, and weakness. Genetic factors and the inability of the human body to deal with certain chemicals and hormones, and feelings of hopelessness can contribute to anger. The main purpose of the study was to assess the effectiveness of deep breathing exercise and meditation on stress and anger management expression among adolescent nursing students. Method: The study employed a quantitative approach utilizing a pre-experimental design with a single-group pre-test post-test design. The selection of participants employed purposive sampling, a non-probability technique, while data gathering utilized a structured questionnaire. The research data were analyzed using both statistical and descriptive methods. Results reveal that computed value (60.232) was higher than table value (2.000) at the level of significance, which indicates that the intervention given for stress management was effective for adolescent nursing students. Conclusion: The findings of the study concluded that deep breathing exercise and meditation for stress and anger management was effective among adolescent nursing students.
Keywords: Assessment; Meditation; adolescent; anger; deep breathing; stress